Michelle Obama’s Becoming as a Political Memoir: A Gramscian Approach - Shrestha, Tara Lal (SCHOLARS: Journal of Arts & Humanities, 2020)
When one internalizes the truth that nothing is beyond the politics of hegemony, the counter-hegemoinic discourse exists as strategic essentialism. As such, the influence of hegemonic discourses as represented by the dominant group gets transferred to the dominated mass inferior group. Derogatory terms towards racial minorities, to the African-Americans in particular, have been internationalized with generalization. Michelle Obama’s 2018 autobiography Becoming unearths such deep-rooted dynamics of dehumanization of minorities persisting in her country where racism enclosed with patriarchy is still dominant in newer forms in everyday life. Indifferent to politics in her early phase of life, she gradually gets metamorphosed into an activist intellectual. She stands along with some critics to defend that America did not enter into the ‘postracial era’ even after Barack Obama served the White House as the President for two terms. She looks in search of ‘organic’ intellectuals who assume the integral politicization of a practical intellectual role as the permanent persuader to preserve achieved minority rights in the context of the rise of Donald Trump in American politics. Her memoir, having political febrics, therefore, presents a counterhegemonic essence.